2012
DOI: 10.1002/cphc.201100732
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Chemistry of Water on Fe(100): A Density Functional Theory Study

Abstract: The formation of water by hydrogenation of atomic oxygen is studied using density functional theory. Atomic oxygen preferentially adsorbs at the four-fold hollow site, the hydroxyl group prefers the bridge site in a tilted configuration, and water is most stable when adsorbed at the top site with the two O-H bonds parallel to the Fe surface. Water formation by the hydrogenation of oxygen is a highly activated process on the Fe(100) surface, with similar activation energies, in the order of 1.1 eV, for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 36 publications
11
28
1
Order By: Relevance
“…In previous works [37][38][39], adsorptions of neutral molecules were considered negligible as compared with those of atoms and radicals. Literature calculations suggest that the adsorption of water on surface iron atoms can take place without a barrier [89,90]. However, model simulations with this assumption, including the subsequent reactions of adsorbed water, lead to relevant discrepancies with our experimental results, which are accounted for much better by assuming no H 2 O adsorption.…”
Section: Modelcontrasting
confidence: 62%
See 1 more Smart Citation
“…In previous works [37][38][39], adsorptions of neutral molecules were considered negligible as compared with those of atoms and radicals. Literature calculations suggest that the adsorption of water on surface iron atoms can take place without a barrier [89,90]. However, model simulations with this assumption, including the subsequent reactions of adsorbed water, lead to relevant discrepancies with our experimental results, which are accounted for much better by assuming no H 2 O adsorption.…”
Section: Modelcontrasting
confidence: 62%
“…However, model simulations with this assumption, including the subsequent reactions of adsorbed water, lead to relevant discrepancies with our experimental results, which are accounted for much better by assuming no H 2 O adsorption. Likewise the LangmuirHinshelwood heterogeneous recombination of adsorbed reactants like OH(s) + H(s) or 2 OH(s) for water production, with predicted energy barriers of ~ 1.1 eV and ~ 0.65 eV [89], respectively, have been considered minor, as compared with the barrierless Eley-Rideal processes listed in table 2 and have not been included in the final modelling.…”
Section: Modelmentioning
confidence: 99%
“…These are higher compared to previously reported values for the Fe(1 1 0) surface [57], which are $60 kJ/mol and 70 kJ/mol for the first and second H additions. Govender et al demonstrated that water formation on Fe(1 0 0) can also occur by reaction of two OH groups [27]. This step appears less likely on the carbide surfaces.…”
Section: Ch 4 Formationmentioning
confidence: 97%
“…Among the mixture of carbide and oxide phases [5][6][7][8] present under process conditions, the Hägg carbide (v-Fe 5 C 2 ) is generally regarded as the active phase for FTS [2,5,6,[9][10][11][12][13][14][15][16][17][18], although other phases such as e-Fe 2.2 C or h-Fe 3 C may exhibit activity as well [9]. Mechanistic studies on CO hydrogenation and FTS on metallic iron surfaces are available in the literature [4,14,[19][20][21][22][23][24][25][26][27][28][29], but studies on the catalytic properties of iron carbides in FTS are scarce, we refer to de Smit and Weckhuysen [13] for a recent review and to other literature [3,5,[8][9][10][11]13,15,24,[30][31][32][33][34][35]…”
Section: Introductionmentioning
confidence: 99%
“…For the O species, Govender et al [35] have found that the hcp and bridge sites were equally stable. On the other hand, Błoński et al [60] and Lu et al [30] suggested that O atom only occupied the hollow hcp sites.…”
Section: Adsorption Of H 2 O Oh O and H On The Clean Fe(100) Surfacementioning
confidence: 99%